2000
DOI: 10.1007/s002700010066
|View full text |Cite
|
Sign up to set email alerts
|

Failing Hemodialysis Arteriovenous Fistula and Percutaneous Treatment: Imaging with CT, MRI and Digital Subtraction Angiography

Abstract: CT and MRI can provide information regarding the degree of vascular impairment, helping to stratify patients into those who can have PTA (single or multiple stenoses) versus those who require an operative procedure (occlusion). Conventional angiography can be reserved for candidates for percutaneous intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Gadolinium-based contrast material-enhanced MR angiography methods are generally contraindicated in this patient population (2), given the association between gadolinium use and nephrogenic systemic fibrosis in end-stage renal disease patients (3-5) Although gadolinium can be administered in emergent situations where the benefit outweighs the risk, particularly when dialysis can be performed immediately following gadolinium use, it is still unsuited for more routine monitoring needs. The feasibility and diagnostic value of nonenhanced time-of-flight (TOF) MR angiography has been demonstrated for AVFs (6)(7)(8). However, TOF imaging is dependent on blood flow conditions, and flow complexities in tortuous AVF geometries can result in poor image quality and inaccurate assessment of the vascular geometry.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Gadolinium-based contrast material-enhanced MR angiography methods are generally contraindicated in this patient population (2), given the association between gadolinium use and nephrogenic systemic fibrosis in end-stage renal disease patients (3-5) Although gadolinium can be administered in emergent situations where the benefit outweighs the risk, particularly when dialysis can be performed immediately following gadolinium use, it is still unsuited for more routine monitoring needs. The feasibility and diagnostic value of nonenhanced time-of-flight (TOF) MR angiography has been demonstrated for AVFs (6)(7)(8). However, TOF imaging is dependent on blood flow conditions, and flow complexities in tortuous AVF geometries can result in poor image quality and inaccurate assessment of the vascular geometry.…”
Section: Mr Imagingmentioning
confidence: 99%
“…Contrast-enhanced MRA, which does not involve radiation, has been used for evaluating dysfunctional AVFs, with impressive results. 16,19 Unfortunately, concerns about a possible relationship between gadolinium-based contrast agents and nephrogenic systemic fibrosis (NSF) have brought into question the use of these agents for MRA. 20,21 Although this relationship has not been conclusively proven, an association has been seen in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gadolinium-based contrast materialenhanced MRA may be nephrotoxic in patients who have impaired renal function. 12e14 Non-enhanced time-of-flight (TOF)-MRA has been used for imaging AVFs, 15,16 but disturbed flow near the stenosis may result in an inaccurate assessment of the fistula geometry. Black-blood (BB)-MRA can clearly display the vascular geometry with the use of flow suppression techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, Lin et al [10] used single-slice CT angiography (SSCTA) to evaluate the vascular access in 9 hemodialysis patients and made comparison with results obtained with DSA and found that CT angiography correlated closely with DSA and spared some of the shortcomings of DSA. In another clinical study, Cavagna et al [11] compared the results of SSCTA, magnetic resonance angiography, and DSA in 13 patients in their evaluation of failing hemodialysis AVF and drew the conclusion that CT and magnetic resonance angiography can provide information regarding the degree of vascular impairment. However, the quality of images using SSCTA was much poorer, and the examination time was longer as compared with MSCTA.…”
Section: Discussionmentioning
confidence: 99%